Total hip replacement after prior of the core decompression of the femoral head: efficacy and complications - M. A. Panin; N. V. Zagorodnii; A. V. Boiko; A. S. Petrosyan (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. A history of core decompression using porous tantalum rods has a negative impact on the course of total hip arthroplasty surgery, the postoperative period and the frequency and nature of postoperative complications. Opinions are contradictory with regard to the effect of other techniques of necrosis decompression on total hip arthroplasty.Purpose of the study: evaluation of the effect of core decompression of the femoral head on the intraand postoperative parameters of total hip arthroplasty surgery.Object and methods. The study included 44 patients with osteonecrosis of the femoral head who underwent total hip arthroplasty. The first group consisted of 30 patients with osteonecrosis of the femoral head (ARCO grade II-IV) who had no previous hip surgery – primary total hip arthroplasty. The second group included 14 patients with osteonecrosis who had undergone the core decompression on the same joint (secondary total hip arthroplasty) 6–24 months earlier in stage II of the disease. The duration of surgery, blood loss volume, complications in the postoperative period, pain syndrome dynamics and hip joint function were assessed.Results. Comparative analysis showed the absence of significant technical intraoperative complications in total hip arthroplasty: duration of operations in group I – 85 ± 25 minutes, in group II – 80 ± 20 minutes, that is, almost identical; volume of intraoperative blood loss: 300 ± 100 ml in both groups. Survival rate of the hip replacement was 100 % in both groups. Superficial inflammation of the operating wound was diagnosed in 3.3 % of group I patients and in 7.1 % of group II patients (%). Dislocation of the hip replacement was observed in one patient in Group I (primary total hip arthroplasty). Twelve months after THA, osteolysis around the hip replacement element was detected by X-ray in 6.7 % of group I patients.Conclusion. Total hip arthroplasty in patients with a history of the core decompression of the femoral head is not accompanied by intraoperative technical difficulties and is a relatively safe surgical intervention. Prior core decompression is not an additional risk factor for intraand postoperative complications of total hip arthroplasty.